Prevention of venous thromboembolism in ambulatory patients with cancer. Issue 6 (23rd November 2020) - Khorana, Alok A; Cohen, Alexander T; Carrier, Marc; Meyer, Guy; Pabinger, Ingrid; Kavan, Petr; Wells, Philip S
Abstract : Patients with cancer are at high risk of venous thromboembolic events, and this risk can be further increased in patients with certain cancer types and by cancer treatments. Guidelines on the prevention of cancer-associated thrombosis (CAT) recommend thromboprophylaxis for hospitalised patients; however, this is not routinely recommended for ambulatory patients receiving chemotherapy and is limited to specified high-risk patients. Identification of the ambulatory patients at risk of CAT who would most benefit from anticoagulant therapy is therefore critical to reduce the incidence of this complication. For patients receiving thromboprophylaxis for CAT, treatment options include low molecular weight heparin, acetylsalicylic acid, warfarin or direct oral anticoagulants (apixaban or rivaroxaban), dependent on the cancer type and cancer treatment regimen. This review discusses emerging clinical trial data and their potential clinical impact.